Gaya Berpakaian di Media Sosial pada Remaja Perempuan di Pendopo Talang Ubi Kabupaten Penukal Abab Lematang Ilir - Sujatmiko, Werdo; Hendarso, Yoyok; Idi, Abdullah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Technological advancements have significantly influenced human life, making it inseparable from their impact, particularly in the realms of information and communication, especially through social media. Social media platforms enable individuals to learn about various widely discussed phenomena, including fashion trends among teenage girls. This research aims to understand and analyze the dressing styles of teenage girls in Pendopo Talang Ubi, Penukal Abab Lematang Ilir Regency, as reflected on social media. The study employed qualitative descriptive research methods with a phenomenological approach, utilizing data collection techniques such as documentation, in-depth interviews with purposively selected informants, and observation. This research indicated that the clothing styles adopted by teenage girls in Pendopo Talang Ubi, Penukal Abab Lematang Ilir Regency, were closely related to and influenced by social media. The positive impacts of this phenomenon included enhanced self-confidence and creativity, the development of relationships and popularity, and financial benefits. Conversely, the negative impacts encompassed social pressure, cyberbullying, consumerism, and concerns regarding the safety of social media environments.